Analysis of Information Security Management Systems at University - Bierhoff Parengkuan, Kenny Tatauhe , Fanny Worotijan (JR Education, 2021)
One of the keys to the success of securing information systems is the vision and commitment of top management leaders. Security efforts or initiatives would be meaningless without them. In the absence of commitment from top management, the impact on data security investment. In addition, success is also determined such as the process of design, implementation, configuration, and use. For this reason, adequate standards and management are needed so that security can be carried out adequately. Competency standards can be carried out in accordance with TKTI if using National standards. Competency standards do not mean only the ability to complete a task, but are also based on how and why the task is done. In addition, the ISO standard which is an international standard can be applied using ISO 17799. Security operations management must fulfill several important things, namely control and protection, monitoring and auditing, as well as an understanding of threats and vulnerabilities.